2007
DOI: 10.11120/ital.2007.06040004
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Program: Going Pair-Shaped

Abstract: Students continue to struggle with learning to program. Not only has there been a significant drop in the number of students enrolling in IT courses, but the attrition rate for these courses continues to be significant. Introductory programming subjects in IT courses seem to be a stumbling block for many students. How do we best engage students in the learning of a programming language? How can our current teaching and learning methods be improved to provide a better experience for them?Issues that have a detr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…In such a situation, students within the collaborative small group were linked together, held accountable for the group's work, received help and assistance from each other, shared resources and materials, and provided each other with feedback in order to successfully perform the group activity. This explanation is also consistent with the results of other studies (Benaya & Zur, 2007;Kalayci & Humiston, 2015;McKinney & Denton, 2006;Teague & Roe, 2007) which showed that the integration of collaborative activities into online computer science courses benefits student learning as well as the development of skill sharing. Another explanation for the above finding may be that the students of the experimental group, unlike students of the control group, participated in two levels of discussions: the small group DF and the central DF.…”
Section: Discussionsupporting
confidence: 92%
“…In such a situation, students within the collaborative small group were linked together, held accountable for the group's work, received help and assistance from each other, shared resources and materials, and provided each other with feedback in order to successfully perform the group activity. This explanation is also consistent with the results of other studies (Benaya & Zur, 2007;Kalayci & Humiston, 2015;McKinney & Denton, 2006;Teague & Roe, 2007) which showed that the integration of collaborative activities into online computer science courses benefits student learning as well as the development of skill sharing. Another explanation for the above finding may be that the students of the experimental group, unlike students of the control group, participated in two levels of discussions: the small group DF and the central DF.…”
Section: Discussionsupporting
confidence: 92%
“…One of the obvious places to address this skills shortage is at the undergraduate stage which students have traditionally found difficult to complete successfully. There is no shortage of innovation in teaching techniques to try something different, for example pair programming (Teague & Roe, 2007) and problem-based learning (O' Kelly et al, 2004;.…”
Section: Introductionmentioning
confidence: 99%
“…In computer programming, much effort has been put into changing the curriculum; for example, introducing pair programming (Teague & Roe, 2007) and problem-based learning (O' Kelly et al, 2004a;O'Kelly, Mooney, Bergin, Gaughran, & Ghent, 2004b). With the evolution of learning analytics, it has become possible to explore the effect of such curriculum changes, and student behaviour in general, at an unprecedented level of detail.…”
Section: Prior Workmentioning
confidence: 99%